When and where should there be dedicated lanes under mixed traffic of automated and human-driven vehicles for system-level benefits?. (September 2020) - Kumar, Amit; Guhathakurta, Subhrajit; Venkatachalam, Sneha
Abstract: Automated vehicle (AV) technology is rapidly moving towards reality and will be mature within the next decade. However, the physical, institutional, and legal infrastructure for enabling widespread adoption of this technology are still lagging significantly. The focus of this research is on developing a decision framework for optimal upgrading of the road network for mixed AV and conventional (NAV) traffic. Given that AVs will undoubtedly share a large segment of the current road network with conventional traffic for the foreseeable future, how the network can be retrofitted to optimize flow of all traffic is a critical issue. Of particular interest are questions regarding when and where the provision of dedicated lanes for AVs can offer benefits for all traffic, and at what level of AV adoption this investment becomes cost-effective. Answers to these questions are critical for planning the future transportation system. We use the term autonomous vehicle to indicate that they can not only drive without human interference using sensing technology but can also communicate with other vehicles and road infrastructure. While the technology is progressing rapidly, planning infrastructure investments and enhancements to optimally harness the benefits of AV technology capabilities merits serious attention. Specifically, the use of dedicated lanes to accommodate AVs so that they may platoon is an important consideration from a policy as well as planning perspective. The proposed study investigates this issue to determine when and where dedicated AV lanes would provide the maximum benefit to all traffic and make such infrastructure investments cost effective.